THE SUPPORTERS' STATUTE INTERFERENCES ON BRAZILIAN SOCCER CHAMPIONSHIP: MATCHES HELD IN CURITIBA (Fiep Bulletin - online, 2013)
This article aims to demonstrate the research, cataloging, tracking, analysis and dissemination of information on the issues listed by the supporters' statute in the Brazilian Soccer Championship held in Curitiba. The research passed in 2006 and 2007, in the stadiums of Curitiba (Couto Pereira, Vila Capanema and the Baixada Arena), belonging respectively to the three main football clubs of the State of Parana (Coritiba Football Club, Paraná Clube and Clube Atletico Paranaense), taking as the focus of analysis three issues that were part of a questionnaire developed by the Ministry of Sports. This questionnaire was used among fans during the matches, in order to identify the perception of these in relation to the provisions specified in supporters' statute. It should be noted that the research had the support network of CEDES (Center for the Study and Development of Sport and Leisure), funded by the Ministry of Sports and universities comprised the six states that have representatives in the Series A of the Brazilian Soccer Championship
Keywords: State; soccer supporters' statute